RESTORATION OF ELEMENTS IN THE FACADE DECOR OF MONUMENTS IN ARCHITECTURE - Neshchadym, Vladyslav (Теорія та практика дизайну, 2023)
The restoration of elements in the facade decor of monuments in architecture refers to the process of repairing or reconstructing the decorative elements on the exterior of a building or monument, with the aim of restoring its original appearance. Facade decor can include a wide variety of elements, such as statues, carvings, friezes, cornices, balustrades, and other ornamental details. Over time, these elements can become damaged or deteriorate due to exposure to weather, pollution, and other environmental factors. They may also suffer damage from human activities such as vandalism or war. Restoration of facade decor typically involves careful assessment of the condition of the elements in question, including the materials used, the level of damage, and the original design. The restoration process may involve cleaning, repair, reconstruction, or replacement of the damaged elements. The goal is to ensure that the restored elements match the original design and materials as closely as possible, while also addressing any structural issues or safety concerns. Restoration of facade decor is an important aspect of preserving historical architecture and cultural heritage. It requires specialized knowledge and skills in areas such as conservation, art history, and architectural design. In many cases, restoration work is carried out by teams of experts and may require significant funding and resources. However, it is considered an essential investment in the preservation of our built environment and cultural heritage for future generations to enjoy. The article presents the results of the study of special computer technology for the restoration of architectural monuments, namely the process of acquiring point information for the construction of a 3D model of an element of facade decoration. An algorithm was developed to detect and eliminate “shadowed” areas of the scanned relief surface. Scanning accuracy and determination of the maximum possible scanning range are studied on the example of a sphere. Restorative reproduction of the elements of the facade decor according to its model requires a fairly high accuracy, which is determined by the requirements for primary geometric information (point cloud). Such information is obtained as a result of iterative laser scanning of the reproduced relief surface from certain points according to a special algorithm that sets the trajectory of the laser beam and the point fixation mode.